2021
DOI: 10.1016/j.jaapos.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment on retinal microvasculature in children with unilateral amblyopia

Abstract: To assess whether the abnormal retinal microvasculature in unilateral amblyopia changes following amblyopia treatment. METHODSA total of 70 patients with unilateral amblyopia (4-12 years of age) were initially recruited. Of these, 33 completed follow-up assessments after 6 months of amblyopia treatment. The retinal thickness and microvascular metrics were measured at baseline and after treatment. The interocular differences and longitudinal changes after treatment were analyzed. Partial correlation analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Indeed, the lack of correlation between fixation stability and the FAZ area has been previously reported for other retinal pathologies [26][27][28], but, as far as we know, it has not been explored in amblyopia. Similarly, the FAZ area was not correlated with BCVA, in contrast with the report by Huang et al (2021) [31], in which the authors observed an improvement in both visual acuity and FAZ area following 6 months of amblyopia treatment.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Indeed, the lack of correlation between fixation stability and the FAZ area has been previously reported for other retinal pathologies [26][27][28], but, as far as we know, it has not been explored in amblyopia. Similarly, the FAZ area was not correlated with BCVA, in contrast with the report by Huang et al (2021) [31], in which the authors observed an improvement in both visual acuity and FAZ area following 6 months of amblyopia treatment.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the relationship between fixation stability and specific retinal anatomical features in various types of amblyopia is not conclusive. Similarly, several studies have investigated differences in the FAZ area between amblyopic and contralateral eyes, as well as healthy controls, reporting contradictory evidence [10,12,[29][30][31][32]. These discrepancies may be due to variations in sample demographics, such as age (adults or children) and distribution of amblyopia types, as well as differences in instrumentation, analysis software and methodology.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, it is one of the first longitudinal study to attempt to compare microvascular parameters before and after patching therapy. While Gunzenhaiser et al 29 showed there was a significant increase in retinal vessel density in 3 × 3-mm scans after treatment, Huang et al 30 didn’t find significant longitudinal changes in VD or PD.…”
Section: Discussionmentioning
confidence: 96%
“…A value closer to 1 indicated a more regular circular shape. We assumed that the circularity of the FAZ at baseline was 0.7 ± 0.1 in the eye with amblyopia, and four months after amblyopia treatment, it was 0.8 ± 0.12, as reported by Huang et al 14 We ensured high-quality scan with an experienced technician trained by the OCTA company. The built-in software automatically rejected scans if the artifacts affected the interpretation of the scan results.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 33 amblyopic children in China revealed that the area and circularity of the FAZ decreased after six months of amblyopia therapy, and the latter was well correlated with an improvement in visual acuity in treated eyes. 14 …”
Section: Introductionmentioning
confidence: 99%